(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
This article aims to study the press discourses about Northpatagonic young women at the beginning of the 21st century. It analyses a heterogeneous corpus of news and reports from the Río Negro newspaper seeking the meanings that are constructed and spread about what it is to be a young woman. Critical Discourse Analysis (Fairclough, 1992, 2003, among others) and Feminist CDA (Lazar, 2005 and Mills, 2008) are both the theory and the methodology employed to explain the semiotic and discursive mechanisms used by the newspaper to create those meanings.